Chapter Poesia del Gulag o della zona? Problemi e prospettive di analisi per una descrizione del corpus poetico dei prigionieri politici in URSS - Pieralli, Claudia (Biblioteca di Studi Slavistici, 2017)
The present survey aims at creating the basis for an extensive study on poetry written by victims of political repressions in the whole area of Segregation in the Soviet Union: prisons, forced labour camps, Gulags and confinement. The research relies on evidence drawn from published and archive materials, concerning the 1918-1956 period. We propose a systematization of the corpus, based on a new methodology: the key-concept of 'poetry of Zone' as a literary track of testimony of political repression, which was synchronical to the imprisonment experience in the USSR.